Pengaruh Pemahaman Keagamaan, Etos Kerja Islam, Kedisiplinan, Tanggung Jawab, dan Pendidikan Terhadap Profesionalitas Kinerja Karyawan pada Perusahaan Asuransi Syariah di Kota Samarinda - Khairul Rizal; Parno Parno; Kokom Komariyah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
This research aims to find out how much religious understanding, Islamic work ethic, discipline, responsibility, and education affect the professionalism of performance in sharia insurance employees in Samarinda City. The research method used in this study is quantitative research, with a population of 16 respondents from 3 Islamic insurance companies in Samarinda and all employees became respondents. The data instruments used in this study are validity test with product moment correlation formula, reliability test, classic assumption test, with analysis of multiple linear regression test data, partial test (t test), and f test, where to see the effect that occurs between variables free, religious understanding, Islamic work ethic, discipline, responsibility, and education (X) with dependent variable on employee performance (Y). The results of this study indicate data analysis, religious understanding variables, Islamic work ethic, and education do not have a significant effect on the professionalism of employee performance. While the discipline and responsibility variables have a significant influence on the professionalism of employee performance. Then the variables of religious understanding, Islamic work ethic, discipline, responsibility, and education together (simultaneously) have a significant effect on the professionalism of employee performance